1994
DOI: 10.1177/019394599401600202
|View full text |Cite
|
Sign up to set email alerts
|

Things That Help and Hinder Adolescent Sibling Bereavement

Abstract: A taxonomy of the things that help and hinder adolescents' sibling bereavement was developed from the responses of 140 bereaved adolescents to the questions What helped you cope with your sibling's death? and What made it harder to cope with your sibling's death? The dichotomous taxonomic framework revealed five categories. The categories of self, family, friends, social system, and time contained descriptions of things that helped coping. The categories of self, family, and social system also included descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
57
2
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 19 publications
8
57
2
1
Order By: Relevance
“…It is apparent that siblings in bereaved families are in a precarious position: not only do they lose their expected sister or brother; the results provide insight into how the loss meant a loss of their parents as well, thus the parents were preoccupied with their own grief and not being able to attend to their needs, a result consistent with previous research (Hogan & DeSantis, 1994). In addition, the adolescents are in some way forgotten when most people pay attention to the parents, or adolescents feel as though they have to withdraw their grief so that they do not become more of a burden to their already overburdened parents.…”
Section: Discussionsupporting
confidence: 84%
“…It is apparent that siblings in bereaved families are in a precarious position: not only do they lose their expected sister or brother; the results provide insight into how the loss meant a loss of their parents as well, thus the parents were preoccupied with their own grief and not being able to attend to their needs, a result consistent with previous research (Hogan & DeSantis, 1994). In addition, the adolescents are in some way forgotten when most people pay attention to the parents, or adolescents feel as though they have to withdraw their grief so that they do not become more of a burden to their already overburdened parents.…”
Section: Discussionsupporting
confidence: 84%
“…These added loss-oriented stressors could complicate grief, as the insensitivity of others can hinder the bereavement process (Hogan, De Santis, Demi, Cowles, & Ross, 1994). Facebook connects the bereaved to others in their community, both sensitive and insensitive, making the social context of grief even more public and communal (Walter et al, 2012).…”
Section: Communitymentioning
confidence: 99%
“…For example, in a study of early parental adjustment after the death of a child from cancer, parents noted the importance of: maintaining a relationship with the deceased child (i.e., continuing bonds); relying on significant others, family, and friends for stability and support; and keeping busy by focusing on both old and new routines (Barrera et al, 2007; Barrera et al, 2009). Adolescents whose siblings died up to five years earlier reported that: stress-reducing activities, personal belief systems/religion, support from parents, extended family, and friends, organized peer support groups and professional support (e.g., psychologists and ministers), and time were most helpful in coping with the death of their brother or sister (Hogan & DeSantis, 1994). Another study indicated that adolescents who lost a sibling to cancer seven to nine years earlier spoke positively of: spending time with their sibling prior to his or her death; sharing the death experience with others; recalling memories of their sibling; and relying on family for emotional support (Martinson & Campos, 1991).…”
mentioning
confidence: 99%
“…According to Klass and colleagues (1996), these connections can provide comfort, ease the transition from the past to the future, and facilitate coping strategies for both adults and children. However, continuing bonds have also been associated with more grief symptoms and adjustment difficulties (Boelen, Stroebe, Schut, & Zijerveld, 2006; Hogan & DeSantis, 1994; Neimeyer, Baldwin, & Gillies, 2006; Normand, Silverman, & Nickman, 1996), which suggests that the role and impact of maintaining connections with the deceased is complex for some individuals.…”
mentioning
confidence: 99%